The Use of Animals as Traditional Medicine in Tanah Bawah, Kimak, and Silip Villages - Syafutra, Randi; Dalimunthe, Nurzaidah Putri; Priyansah, Sujadi; Al Farizi, Muhammad; Saputri, Nelsa; Muhtadin; Ramadhani; Alamsyah, Candra; Juliansyah, Andika; Saputra, Baruna; Tendri; Wibawa, Ahmad Juliyanta (Universitas Nusa Bangsa, 2025)
Kimak, Tanah Bawah, and Silip are three villages in Bangka Regency, Bangka Belitung Islands Province, Indonesia, where animals are still used for traditional medicine. This study aimed to collect, analyze, and evaluate data on the use of animals in traditional medicine by the communities of Kimak, Tanah Bawah, and Silip. The research was conducted over three months, from March to May 2024. Data collection involved surveys and informant selection using the snowball sampling method. Fifteen selected informants were interviewed based on a prepared questionnaire. Data analysis was carried out qualitatively (using descriptive statistics) and quantitatively (calculating the Relative Frequency of Citation (RFC) and Informant Consensus Factor (ICF)). The results showed a positive correlation between informants’ age and their knowledge of animal-based traditional medicine, with informants over 45 years old possessing broader knowledge due to their longer life experiences. Dependence on traditional medicine was influenced by limited access to modern healthcare services and the cultural and spiritual significance of these practices. A total of 14 animal species from five classes were used, with Mammalia being the most dominant class (35.7%). Malayopython reticulatus had the highest RFC value (0.667), while species with the lowest RFC values (0.067) included Nisaetus cirrhatus, Galeopterus variegatus, Trachypithecus cristatus, and Nesolagus netscheri. The most commonly used body part was meat. ICF analysis indicated that disease categories such as skin ailments, internal injuries, nerve disorders, ulcers, hemorrhoids, and mental illnesses had the highest levels of informant consensus. Several used species are classified as threatened, highlighting the need for stronger conservation efforts through collaboration between the government, conservation organizations, and local communities. Balancing conservation with traditional medicine practices is essential to preserving cultural heritage while supporting ecological sustainability.